KDR polymorphism (1192G/A, 1719A/T) and modulation of ARV drug-induced hepatotoxicity. (December 2021) - Singh, HariOm; Samani, Dharmesh; Jadhav, Sushama
Abstract: Kinase insert Domain containing Receptor (KDR)/Vascular Endothelial Growth Factor Receptor (VEGFR-2) participate in endothelial dysfunction, which can lead to chronic liver disease. KDR reflects naturally against the toxicants from the damaged liver cells. Association of KDR polymorphism has been reported with many diseases including liver disease, but its role has not been described in ARV induced hepatotoxicity. Hence, we examined the exonic regions KDR (1192G/A, 1719A/T) polymorphism from 165 HIV-infected individuals (34/165 had ARV induced hepatotoxicity, 131/165 were with no hepatotoxicity) and 160 normal uninfected individuals by PCR-RFLP. In univariate analysis, KDR 1719 TT genotype presented at greater frequency from all HIV positive individuals in contrast with normal uninfected individuals (7.87% vs. 4.4%, OR = 1.72, P = 0.38). Individuals with KDR 1719 TT genotype had a risk for increasing hepatotoxicity and its severity (OR = 1.91, P = 0.38). Individuals with haplotype AT had risk for increasing hepatotoxicity and its severity (OR = 1.60, P = 0.50; OR = 2.35, P = 0.27). Whereas haplotype AA was associated with reduced risk of developing hepatotoxicity (OR = 0.40, P = 0.04). Individuals with KDR 1719 TT genotype were at greater risk of advancement of HIV disease (OR = 2.31, P = 0.23). Individuals with KDR 1719 TT genotype had more vulnerability for developing hepatotoxicity among alcohol users (OR = 2.57, P = 0.23). Individuals with KDR 1719 TT genotype were at higher risk of developing hepatotoxicity and its severity among nevirapine and alcohol consumers (OR = 2.47, P = 0.24; OR = 5.42, P = 0.42). In multivariate analysis, hepatotoxicity patients taking ART inclusive of nevirapine was associated with the severity of hepatotoxicity (OR = 4.82, P = 0.002). In conclusion, KDR 1719 TT genotype and haplotype AT may have a risk for development of hepatotoxicity and its severity. Haplotype AA may have influence to reduce the risk of developing hepatotoxicity. Highlights: Individuals with KDR 1719 TT genotype and haplotype AT may have a risk for development of hepatotoxicity and its severity. Haplotype AA may have influence to reduce the possibility of developing hepatotoxicity. Individuals with KDR 1719TT genotype taking alcoholic and nevirapine might help in the development of ARV induced hepatotoxicity.